Comment regarding the paper "Solubility determination and thermodynamic modelling of 3, 5-dimethylpyrazole in nine organic solvents from T = (283.15 to 313.15) K and mixing properties of solutions". (January 2019) - Yuan, Yang; Xu, Renjie; Zhao, Hongkun
Highlights: Errors are found in model coefficients for mathematical representations. NRTL model coefficients fail to back-calculated observed solubility. Coefficients of NRTL model were re-analyzed. Abstract: Errors were discovered regarding the published equation coefficients of Yao and co-workers (2017) for mathematically describing the solubility of 3, 5-dimethylpyrazole in nine organic solvents using the NRTL model. Larger differences were found between our back-calculated data and those reported in the authors' published paper. The equation parameters were re-regressed based on the reported solubility data.